Note—A Note on the Use of the CAPM as a Strategic Planning Tool - Boardman, Anthony E.; Carruthers, Norman E. (Management Science, 1985)
A recent paper by Naylor and Tapon (Naylor, Thomas H., Francis Tapon. 1982. The capital asset pricing model: an evaluation of its potential as a strategic planning tool. Management Sci. 28 1166–1173.) showed that the capital asset pricing model (CAPM) can be an important strategic planning tool, but their specific strategic suggestions were incorrect. The proper conclusion to draw from the CAPM is that a company should purchase a business if its expected return exceeds the expected return in equilibrium of a business in the same risk class. In the absence of synergy, each potential acquisition should be evaluated on its own merit, independent of the other businesses in a company's portfolio. When all firms are in equilibrium, no gain may be made from merger or takeover.